BARRIERS TO INNOVATION AND COMPETITIVENESS: A CASE STUDY OF RATTAN CRAFT AND FURNITURE SMES IN ACEH - Ummi Safrianti; Sukardi Sukardi; Taufik Djatna (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
Aceh needs to improve industrial growth to secure economic growth by producing innovative products with added value. Some institutions have already put efforts to encourage innovation and development in some SMEs, but they have not showed any progresses. Thus, the aim of this research was to understand what were the barriers that prevent rattan SMEs in Aceh to innovate and become competitive. Previous research looked into barriers to innovation from SMEs owner’s perspectives, however they did not capture barriers from government and university perspectives. A case study research was carried out in SMEs, operating in Aceh Besar Region. This research employed a qualitative study through an explorative interview. The interview data collection used a purposive sampling technique. The result showed that there were three major barriers that were perceived by SMEs owners, namely raw material, financial access, and management and marketing skills. From analytical process the result shows that most of barriers perceived by entrepreneurs interviewed rooted from lack of knowledge transfer and information between triple helix institution. However, from the triple helix analysis, the real problem was the lack of information and different cultures between universities and SMEs. The recommendation that should be best taken by stakeholders in the industry was to transform university to become entrepreneurial university.Keywords: barrier to innovation, competitiveness, rattan SMEs